THE ANALYSIS OF TECHNOLOGY ACCEPTANCE MODEL AND E-TRUST TOWARDS LOYALTY IN TRAVELOKA’S AIRLINES E-TICKETING - Harjanti, Faisha Namira (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to investigate the impact of Perceived Usefulness, Perceived Ease of Use and E-Trust on Customer Loyalty in Traveloka’s Airlines E-Ticketing. This type of study is explanatory research. The questionnaires have been distributed in purposive sampling to 288 student respondents in Faculty of Economics and Business at Brawijaya University. The collected data were processed with Factor Analysis and Multiple Regression Analysis. The finding of Factor Analysis shows that the indicators of Perceived Usefulness, Perceived Ease of Use, E-Trust and Customer Loyalty are qualified to represent or explain the formed variable. Moreover, the results from Regression Analysis reveal that the three independent variables except for Perceived Ease of Use are partially significant on Customer Loyalty. Therefore, it is suggested that to increase the loyalty of customer, companies should improve the trust of customer on Traveloka website which E-Trust is the dominant variable and the usefulness and easiness of products and services should be maintained.Keywords: TAM, E-trust, and Customer Loyalty